2011
DOI: 10.1016/j.febslet.2011.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the substrate binding site in the N-terminal TBP-like domain of RNase H3

Abstract: a b s t r a c tRibonuclease H3 from Bacillus stearothermophilus (Bst-RNase H3) has the N-terminal TBP-like substrate-binding domain. To identify the substrate binding site in this domain, the mutant proteins of the intact protein and isolated N-domain, in which six of the seventeen residues corresponding to those involved in DNA binding of TBP are individually mutated to Ala, were constructed. All of them exhibited decreased enzymatic activities and/or substrate-binding affinities when compared to those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Some residues in the N-domain have been previously predicted to interact with the substrate based on comparisons with TBP–DNA complex structures. Their importance was verified in site-directed mutagenesis studies (30) and is in excellent agreement with our structural data. Alanine substitution of equivalents of the DNA-interacting Tyr43 residue significantly reduced the Mg 2+ -dependent nucleolytic activity in Bst-RNase H3 and Aae-RNase H3 (22,30).…”
Section: Discussionsupporting
confidence: 88%
“…Some residues in the N-domain have been previously predicted to interact with the substrate based on comparisons with TBP–DNA complex structures. Their importance was verified in site-directed mutagenesis studies (30) and is in excellent agreement with our structural data. Alanine substitution of equivalents of the DNA-interacting Tyr43 residue significantly reduced the Mg 2+ -dependent nucleolytic activity in Bst-RNase H3 and Aae-RNase H3 (22,30).…”
Section: Discussionsupporting
confidence: 88%
“…Characterization of the activity of a CpRNase HII -HIII chimeric enzyme Recent structural studies indicated that there is no obvious difference between the structures of RNase HII and HIII except an N-terminal sub-domain in HIII [5,6]. As the results above showed that the 82nd to 88th residues of CpRNase HIII constituted the key part of CpRNase HIII, we tried to add these seven residues of CpRNase HIII to the N-terminus of IIC19…”
Section: Iiin88mentioning
confidence: 99%
“…D IIIN 82-88 with DR 1 D substrate N-terminal extension of Bst-RNase HIII forms N-domain, which is far away from the substrate in the modeled structure of Bst-RNase HIII docked with RNA/DNA hybrid substrate [6]. In the model constructed by Miyashita et al [6], N-domain is rotated around vertical axis by 1308 in a clockwise manner and moves down toward the substrate.…”
Section: Structural Model Of Iic19mentioning
confidence: 99%
See 2 more Smart Citations